2017
DOI: 10.3322/caac.21408
|View full text |Cite
|
Sign up to set email alerts
|

Missed therapeutic and prevention opportunities in women with BRCA‐mutated epithelial ovarian cancer and their families due to low referral rates for genetic counseling and BRCA testing: A review of the literature

Abstract: Answer questions and earn CME/CNE Fifteen percent of women with epithelial ovarian cancer have inherited mutations in the BRCA breast cancer susceptibility genes. Knowledge of her BRCA status has value both for the woman and for her family. A therapeutic benefit exists for the woman with cancer, because a new family of oral drugs, the poly ADP-ribose polymerase (PARP) inhibitors, has recently been approved, and these drugs have the greatest efficacy in women who carry the mutation. For her family, there is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 191 publications
(445 reference statements)
0
69
1
1
Order By: Relevance
“…There is limited awareness of BRCA testing among clinicians/practitioners and the population per se. Low referral rates for genetic counselling and subsequent BRCA testing have been reported by others too, which further highlights the missed therapeutic and prevention opportunities 44. Understanding reasons for differences observed is important and requires further research.…”
Section: Discussionmentioning
confidence: 88%
“…There is limited awareness of BRCA testing among clinicians/practitioners and the population per se. Low referral rates for genetic counselling and subsequent BRCA testing have been reported by others too, which further highlights the missed therapeutic and prevention opportunities 44. Understanding reasons for differences observed is important and requires further research.…”
Section: Discussionmentioning
confidence: 88%
“…National criteria for hereditary breast and ovarian cancer genetic testing do not exist in Canada and each province follows their own formal or informal criteria (see online supplementary file 1). A recent review article by BRCA TtoT members identified process issues, geographic access and lack of physician knowledge as major barriers to genetic testing 26. Current under-referral practices prevent opportunities for personalised treatment of ovarian cancer as well as cancer risk reduction in at-risk relatives.…”
Section: Challenges and Opportunities In Brca1/2 Assessment In Canadamentioning
confidence: 99%
“…31,32 Since stage at presentation can determine surgical management and overall survival, it is crucial to address factors that contribute to women presenting at advanced stages. 33 Interestingly, in our study, only 21 36 There is a hardship program that provides free genetic counseling to those without insurance at BH, yet the process to obtain testing may take several weeks, and results are not often available prior to surgery.…”
Section: Ta B L E 4 Factors Affecting Surgical Treatmentmentioning
confidence: 84%
“…It should also be noted that only 60% of patients at both institutions underwent genetic testing. This could be due to personal preference, health literacy gaps, or lack of insurance coverage . There is a hardship program that provides free genetic counseling to those without insurance at BH, yet the process to obtain testing may take several weeks, and results are not often available prior to surgery.…”
Section: Discussionmentioning
confidence: 99%